Influence of Heat Treatment on Wear and Hardness Properties of MWCNTs Reinforced Epoxy nanocomposites - Al-Rawi , Khalid R.; Madhi, Noor H. (Iraqi Journal of Science, 2022)
Nanocomposite of carbon nanotube add to epoxy resin material of weight fraction ( 0.25, 0.5, 0.75 1.0, 1.25, 1.5, 1.75 , 2 & 2.5 wt. % ) were fabricated by dispersing within an epoxy resin using a Ultrasound machine followed by mechanical stirring. The samples were heat treated at temperature ( 80 °C for 3 hrs) The mechanical properties of the composites were investigated. Wear and hardness properties measurements indicated higher wear rate and hardness with increasing concentration of MWCNTs . The MWCNTs significantly improved the wear resistance and hardness when compare than the pure epoxy. These note show too after heat treatment of composite with ( 80 oC for 3 hrs ).